2016
DOI: 10.1073/pnas.1513023113
|View full text |Cite
|
Sign up to set email alerts
|

Functional evolution of IGF2:IGF2R domain 11 binding generates novel structural interactions and a specific IGF2 antagonist

Abstract: Among the 15 extracellular domains of the mannose 6-phosphate/ insulin-like growth factor-2 receptor (M6P/IGF2R), domain 11 has evolved a binding site for IGF2 to negatively regulate ligand bioavailability and mammalian growth. Despite the highly evolved structural loops of the IGF2:domain 11 binding site, affinity-enhancing AB loop mutations suggest that binding is modifiable. Here we examine the extent to which IGF2:domain 11 affinity, and its specificity over IGF1, can be enhanced, and we examine the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…A different approach for malignancies driven by the IGF-2/IR-A loop is to block IGF-2 using specific antibodies or specific ligand traps. A specific trap for IGF-2 can be obtained using a soluble preparation of the high-affinity domain 11 of M6P/IGF-2R ( 333 , 334 ), while the soluble form of the IGF-1R combined with the Fc portion of IgG1 can provide a trap for both circulating IGF-1 and IGF-2 ( 335 ). These therapies have the advantage to block IR-A stimulation by IGF-2 without impairing the metabolic effects of insulin.…”
Section: Inhibitors Of Insulin/ir-a Signalingmentioning
confidence: 99%
“…A different approach for malignancies driven by the IGF-2/IR-A loop is to block IGF-2 using specific antibodies or specific ligand traps. A specific trap for IGF-2 can be obtained using a soluble preparation of the high-affinity domain 11 of M6P/IGF-2R ( 333 , 334 ), while the soluble form of the IGF-1R combined with the Fc portion of IgG1 can provide a trap for both circulating IGF-1 and IGF-2 ( 335 ). These therapies have the advantage to block IR-A stimulation by IGF-2 without impairing the metabolic effects of insulin.…”
Section: Inhibitors Of Insulin/ir-a Signalingmentioning
confidence: 99%
“…IGF-2 was found to behave as a rescuer in a brief coronary occlusion porcine model and in a sheep model with myocardial infarction 6 ; however, it was later shown to cause Beckwith-Wiedemann syndrome, prenatal overgrowth, poly hydramnios and fetal and neonatal lethality 7 . IGF-2R binds IGF-2 on the cell surface and to mannose-6-phosphate (M6P)-tagged proteins in the trans-Golgi network 8 . It is a type I trans membrane receptor with a large extracellular domain, a relatively short intracellular tail and a trans membrane domain 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, the Hassan group has used further mutagenic alterations of the ligand-interacting surface of M6P/IGF2R domain 11 to generate a refined and improved version of their IGF-II ligand trap, and they have now moved testing of this agent to a xenograft tumor model [ 70 ]. Thus, they showed that treatment with this new ligand trap could inhibit tumor formation by a retrovirally transformed SKNMC Ewing sarcoma cell line that had been selected for dependence on an autocrine IGF-II growth loop [ 70 ]. Their data support the conclusion that the cytostatic effects of such IGF-II ligand-trapping agents may be efficacious in combined anti-tumor therapeutic strategies.…”
Section: Resultsmentioning
confidence: 99%